Virilio and Total Thought - Sean Cubitt (Media Theory, 2019)
This note traces the development of Virilio’s ecological thought from the early Popular Defense and Ecological Struggles into his late writing in The University of Disaster to see how his talismanic concepts increased in resolution and angle of vision over the transition from the later 20th to the early 21st centuries.